IMPLEMENTASI KONSEP TRIPLE NEXUS DALAM UPAYA MEMBANGUN PERDAMAIAN (PEACEBUILDING) SETELAH KONFLIK AMBON-MALUKU - Anju Nofarof Hasudungan (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2021)
This study aims to describe the implementation of the Triple Nexus concept (Humanitarian, Development, Peace) carried out by the United Nations Development Program (UNDP) together with national and local institutions in Maluku. Such as Convey Indonesia, Pusat Pengkajian Islam dan Masyarakat (PPIM) Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, and the Ambon Reconciliation and Mediation Center (ARMC) IAIN Ambon in the peacebuilding process in Ambon-Maluku. This research was conducted using descriptive qualitative research methods. Data was collected through literature study, document analysis, observation, and interviews in January 2018 and July to October 2019. The results showed that the implementation of the Triple Nexus concept in peacebuilding efforts in Ambon-Maluku was very effective and efficient. This can be seen from the refutation of the thesis that the reconciliation process will take decades. The establishment of Ambon-Maluku as a peace laboratory and the most tolerant city after the Ambon conflict is an antithesis. The challenge in the future is the strengthening of identity politics and populism in gaining power that can disrupt peacebuilding.